Antibacterial Activity of Some New Azole Compounds: Antibacteria activity of azole compounds - Hossein Sadeghpour; Zahra Rezaie; Yones Ghasemi; Zahra Falahzadeh; Soghra Khabnadideh (Iranian Journal of Pharmaceutical Sciences, 2012)
We have previously synthesized new N-alkylated azoles (1b-7b) as antifungal agents. Here, we evaluated the antibacterial activities of these compounds against two gram positive and two gram negative bacteria by broth microdilution method. The aminothiazole derivative (7b) showed an excellent antibacterial activity. Other compounds exhibited moderate to good antibacterial activity. All compounds are more active against gram positive than against gram negative bacteria.